L’engagement féministe « en quelques clics » : s’adresser à toutes, se distinguer par la communication - Irène Despontin Lefèvre (Communiquer)
This article examines the claims of political and activist organizations in France in the late 2010s to accessibility and equal participation in the digital age. It will look at the tension between the desire to propose 'inclusive' activism, particularly through communication tools, and the actual participation of its members in a feminist collective, #NousToutes. Organized into three parts, this study will first look at the communicational organization of #NousToutes, and present the mixed qualitative approach on which the study is based. The results will be discussed in the second and third parts. The aim here is to examine how the collective can promote activism that is accessible to as many people as possible thanks to digital tools, based on the effective participation and use of its members.